Fluid attenuation inversion recovery (FLAIR) images of dentatorubropallidoluysian atrophy: case report - Yoshii, F. (BMJ Group, 1998)
The white matter lesions in a patient with late adult onset dentatorubropallidoluysian atrophy (DRPLA) were studied in detail by MRI using the fluid attenuation inversion recovery (FLAIR) technique. The patient was a 60 year old woman with a family history of DRPLA, in whom the number of CAG repeats in the DRPLA gene on chromosome 12 was expanded to 59 (normal allele 10). In addition to atrophy of the cerebral cortex, cerebellum, and pontomesencephalic tegmentum, the cerebral white matter and a part of the white matter tracts within the brainstem showed prominent high signal intensities on FLAIR images. These MR findings suggest that, in addition to the degeneration of the dentatorubral and pallidoluysian systems, the pathological process extends to the white matter in DRPLA. This could be important for differentiating DRPLA from other clinically similar diseases such as Machado-Joseph disease or Huntington's disease.